Las transformaciones de la serranilla entre Edad Media y Renacimiento - Álvaro Alonso (Atalaya)
This article focuses on the evolution of serranilla between 1490 and 1540. During this period, new structural patterns are introduced, such as the supression of the narrative part of medieval pastourelle and the rediscovery of pastorela Compostela, unknown in mediaeval Castile. There are also other changes, visible in the appearance of new situations and psychological attitudes, such as the complicity that arises between the knight and the shepherd. However, there is no reference to the relationship between the knight, the shepherdess and the shepherd, which is recurrent in many French poems.